Academic Libraries and Student Engagement: A Literature Review. Issue 2 (1st October 2020) - Appleton, Leo
Abstract: The term 'student engagement' has a broad meaning and is used freely as an expression in several different contexts of academic librarianship. This literature review covers scholarship from across several of these areas and is structured so that four broad themes are systematically addressed: student engagement in learning; students as partners; student voice; methods and techniques for student engagement. The granular review of the literature reveals many sub-discussions about a range of academic librarianship topics and provides some discussion about how they cross over into the area of student engagement. The literature covers different innovations, techniques and strategies for student engagement, and the review illustrates how many techniques and tools are transferable across the different intentions and objectives of student engagement. The review concludes that many academic librarians are very proactive in student engagement activities and that student engagement itself has become a fundamental element of academic library management.